موا‬‫ئ‬‫مة‬‫النموذج‬ ‫المستخدم‬ ‫في‬ ‫اتخاذ‬ ‫القرارات‬ ‫الإستثمارية‬ ‫مع‬ ‫النم‬‫وذج‬ ‫المستخدم ‬‫في‬ ‫تقييم‬ ‫الأداء‬ ‫الم‫الي ‬‫لمؤسسة‬ صناعية دراسة‬ ‫حالة‬ ‫مطاحن‬ ‫بلغيث‬ ‫مداوروش‬ ‬ ‫س‪/‬ه‬ ‫‪‬‫‬ - منيــة ‫أوفلــة‬‫‬; فطيمــة ‫كبيــر‬‫‬ (My University, 2019)
This study seeks to harmonize or reconcile the discounted cash flow model used in investment decision making, which is one of the best models for making investment decisions, taking into account the time value of money and the model used to evaluate the performance of investment centers on an accrual basis, in proposing As well as the importance of the availability of such harmonization to rationalize decisions and achieve consistency of objectives. To achieve this harmonization by providing for the rate of return on invested capital for each year of the life of the project at the same time as the estimate of expected cash flows, performance is then evaluated against the rate of actual accounting return on capital invested with the expected accounting rate of return Has been calculated, and this is reflected in the mills of Pelghith. ​